Promotion of healthy nutrition in clinical practice: A cross-sectional survey of practices and barriers among physiotherapists in southeast Nigeria - Ukachukwu Okoroafor Abaraogu, BMR (PT); Mary O. Ogaga, BMR (PT); Eric Odidika, BMR (PT); Jose Frantz, PT PhD (World Scientific Publishing, 2016)
Background: Healthy diet counselling is an important concept in health promotion. Physiotherapists are well positioned to initiate or support healthy nutrition in addition to physical activity counselling, in routine patient consultation. Objective: To determine the practices about and barriers to diet counselling practices among physiotherapists in Southeast Nigeria. Methods: In this cross-sectional survey, a total of 140 questionnaires were distributed among physiotherapists. Results: Overall, 103 physiotherapists responded. Physiotherapists are confident and consider the incorporation of dietary counselling very important and of high priority in their daily clinical work. They, however, assessed and counselled on dietary status opportunistically in patients. Notwithstanding, physiotherapists believed that the diet counselling they give could be effective in helping patients change their unhealthy dieting practices. Patients were also amenable to physiotherapists advocating on diet issues as part of their consultation. Several barriers to incorporating diet counselling into physiotherapy practice were identified, including lack of access to a dietician/health promotion staff/counsellors, lack of proper patient education materials, lack of expertise in relation to dietary risk factors' assessment and management, and uncertainty about what dietary services to provide. Conclusion: Although physiotherapists consider it important to incorporate diet counselling in their daily clinical practice, development and implementation of strategies to improve physiotherapists' diet counselling knowledge, competence, skills, and practice are warranted.